Development of a Modular Ratiometric Fluorescent Probe for the Detection of Extracellular Superoxide. Issue 20 (23rd March 2017) - Andina, Diana; Brambilla, Davide; Munzinger, Noah; Frei, Jasmine; Zivko, Cristina; Leroux, Jean‐Christophe; Luciani, Paola
Abstract: Extracellular detection of endogeneous analytes (e.g., superoxide) can provide important insights into mechanisms of homeostasis and diseases, such as tumorigenesis. A ratiometric probe with a fluorescent reference and an analyte‐specific switch‐on dye was developed. Detection of ROS in the extracellular milieu was ensured by connecting the two fluorophores with a modular peptide‐nucleic‐acid‐based linker. The ROS‐sensing ability was assessed and validated in cell‐free assays and in cell culture. Abstract : A ratiometric probe with a fluorescent reference and an analyte‐specific switch‐on dye was developed. Detection of superoxide in the extracellular milieu was ensured by connecting the two fluorophores with a modular peptide‐nucleic‐acid‐based linker.